Investigating Nutritional Behavior and Oral Health Habits among Adults and Children in Nοrth-Eastern Greece - Alexandra Melissari; Athanasios Alexopoulos; Ioanna Mantzourani; Stavros Plessas; Chrissoula Voidarou; Christina Tsigalou; Eugenia Bezirtzoglou (MDPI AG, 2021)
The importance of the oral microbiota is strictly linked to global human health. When imbalance of the oral microbiota occurs, and it is characterized by shifts in bacterial composition and diversity; a state called dysbiosis is settled. There is an increasing amount of scientific evidence that this condition is associated with oral diseases caries, gingivitis and periodontitis. Diet seems to be a key factor for oral and dental health, impacting upon the oral microbiota. In an attempt to clarify the role of diet, as well as other implicating risk factors predisposing to oral disease, in the present study we enrolled an urban area of north-eastern Greece. Socio-demographical as well as hygienic and nutritional habits of a target group consisting of adult and children were entered in our study through a survey. People of the studied area are less interested in preventive and other dental therapies. Children and adults are less interested in healthy eating, yet they often consume sugary foods and often outside of their main meal. The partial shifting to the standard of the Mediterranean diet and less to the standard of the western type foods is notable. It is important to raise the awareness of both children and adults through strategical campaigns and education on oral health, oral hygiene and the benefits of a balanced diet.